Appropriate Budgetary Policy for a Changing Economy - S. P. Solyannikova (Мир новой экономики)
The XXI century's contemporary challenges and crises indicate that fiscal policy is an appropriate tool for countercyclical regulation, ensuring sustainable economic growth and social justice. In this regard, society's requirements for the quality of budgetary policy have changed, which has shifted the focus in setting goals and choosing tools for its implementation from the position of ensuring sustainable economic growth and the principles of fair distribution of income. The analysis allows us to conclude that to ensure the proper quality of budgetary policy, its goals and objectives must correspond to the strategic goals of developing public law education, and coordination of budgetary and monetary policy is necessary. To achieve the goals of justice, the author of the article propose to differentiate the instruments of inter-budgetary reallocation of funds depending on the level of debt sustainability of the regions and to use targeted grants to motivate the authorities of public law entities to ensure sustainable socio-economic development. The article shows that for improvement of the formation mechanism of state programs and national projects and budget efficiency growth, it is necessary to monitor the compliance of tax expenditures and budget subsidies with the target indicators of state programs.